Cognitive profile in older adults in the district of San Isidro-2018 - Huamán Retamozo, Susana Milagros (2018)
The cognitive profile was studied in a sample of 63 elderly people of a social program of the Emmanuel Bible Church in the district of San Isidro - 2018. Using a non-experimental cross-sectional design of a descriptive type, they were administered the Mini’s screening instrument. -mental State Examination MMSE, adapted by Custodio (2008). In addition, a sociodemographic survey was applied to know about the characteristics that older adults present as a reason for research. A profile of mild deterioration was found in the majority of older adults, where the dimensions of evocation, attention and calculation showed a significant decrease in cognitive function. Likewise, they presented statistically significant differences of the cognitive profile in older adults according to sex, age, educational level and marital status.